Final Year Project Guideline - Nawanir, Gusman; Mahmud, Fatimah; Lee, Chia Kuang (Suara UMP, 2020)
The final year project (FYP) is one of the core program subjects in the Bachelor of Project Management (Hons) and Bachelor of Industrial Technology Management (Hons), which is intended to expose the students to the process of conducting academic research in their respective area of study while building communication, presentation, writing, and time management skills.